Plastomes of the subfamily Cactoideae (Cactaceae): genomic, structural and evolutionary aspects - Dalla Costa, Tanara Pletsch (2022)
The family Cactaceae represents the greatest lineage of succulent plants, which contains a set of anatomical, morphological, and physiological modifications allowing adaptation and diversification in arid and semi-arid regions. Cactoideae is the richest subfamily in species diversity within Cactaceae. Representative species of this subfamily, such as Melocactus glaucescens, Lepismium cruciforme, and Schlumbergera truncata demonstrate interesting evolutionary aspects. They have different lifestyles and inhabit places with specific environmental conditions. Their distribution varies from a high degree of endemism and risk of extinction, to wide occurrence and status of extensive ornamental cultivation. Therefore, they are notable species to be used in studies related to plastid genomics. Plastid genomics allows analyzing and understanding phylogenetic and evolutionary relationships at the level of family/subfamily, as well as providing molecular markers that can help in conservation of natural resources. Although few cactus species with complete plastid sequences are available, many unusual features have been identified in the plastomes of the family. Thus, to expand the information concerning plastid evolution in Cactaceae, this study aimed at sequencing, assembling and analyzing the plastomes of M. glaucescens, L. cruciforme, and S. truncata. In addition, to provide complete plastome sequences, enabling analysis of plastome structures, frequency of codon usage, phylogeny, nucleotide diversity hotspots, gene divergence, signatures of positive selection, RNA editing sites and mapping of repetitive sequences. According to the data obtained, the plastomes showed several losses of genes and/or pseudogenization, including essential genes. Pseudogenization of the trnT-GGU gene in L. cruciforme was the first loss of gene functionality reported in the family. Moreover, M. glaucescens lost the trnV-GAC, trnV-UAC (common loss to the subfamily Cactoideae), and trnA-UGC genes, the last two being essential for plastid translation and cell survival, which strongly suggest the importation of tRNAs from the cytosol to the plastids in Cactoideae. Concerning plastomic structures, M. glaucescens showed unique rearrangements that culminated in the expansion of the inverted repeat (IRs) regions, the largest in the subfamily, and the duplication of unusual genes. On the other hand, the analysis of the plastomes of L.cruciforme and S. truncata revealed a conserved structure among the tribe Rhipsalideae, with tribe-specific rearrangements and some variations in the size and content of the IRs. Molecular analyses in plastomes of the family Cactaceae was essential to identify high genetic divergence, numerous signatures of positive selection, and polymorphism of RNA editing sites. Furthermore, hundreds of plastid molecular markers were mapped for the three species, which will be useful for accessing the genetic information of natural populations and conservation of species, especially those threatened. Therefore, this study provides new insights into plastid evolution in Cactaceae, which is an exceptional lineage adapted to extreme environmental conditions and a notorious example of atypical plastome evolution. Keywords: Cactaceae. Plastid evolution. Rearrangements. Gene divergence. RNA editing. Plastid molecular markers.